Pembuatan Pakan Mandiri untuk Masyarakat di Dusun Kalibone Pangkep - Wanebo, Ikhsan; Rauf, Abdul; Murfat, Moh Zulkifli (Window of Community Dedication Journal, 2021)
Kalibone Hamlet, Bonto Langkasa Village, Minasatene District, Pangkep Regency, is dominated by freshwater fish cultivators in rice fields and ponds, especially tilapia. The partner group involved in this activity is the Maminasata fish cultivator group. This group of pond farmers generally cultivate tilapia by providing artificial feed that is purchased at a high enough price so that it becomes a fairly heavy burden in tilapia cultivation activities. Some of the obstacles faced by the group of pond farmers include limited capital to buy feed which is the main input in tilapia cultivation activities, so it is necessary to make efforts to make their own fish feed (independent feed) in order to meet the needs of tilapia feed so that fish farming business can be done continuously.The purpose of this community service activity is to help facilitate tilapia farming groups through training in fish feed making, financial management and feed management, so that efforts to carry out tilapia cultivation can be sustainable and know financial management and proper fish feed management.The method used in the training is a participatory training method, which involves as many partners as possible participation in lectures, discussions, and the practice of design and creation of works. The program that has been agreed with the business group partners is carried out using the training method for making fish feed.The expected output target from the implementation of science and technology through this training is an increase in understanding, knowledge and skills of fish pond farmer group partners on how to make fish feed, financial management and fish feed management.